Visual, hearing, and dual sensory impairment are associated with higher depression and anxiety in women. (19th March 2021) - Pardhan, Shahina; López Sánchez, Guillermo F.; Bourne, Rupert; Davis, Adrian; Leveziel, Nicolas; Koyanagi, Ai; Smith, Lee
Abstract: Objective: We investigated cross‐sectional gender‐specific associations with vision, hearing, and both (dual) impairment with depression and chronic anxiety using a large representative sample of Spanish adults. Methods: The present study utilized data from the Spanish National Health Survey 2017. A total of 23, 089 adults (15–103 years, 45.9% men) participated in this survey. Participants self‐reported whether they had suffered depression and/or anxiety, and also whether they experience vision, hearing and both vision/hearing (dual) impairment. Multivariable logistic regression analyses were conducted to assess the associations between the three types of sensory impairment and anxiety or depression, in men and women. Results: Across the whole sample ( n = 23, 089) the prevalence of depression and anxiety was between 2.00 and 2.56 times higher in women compared to men. Dual sensory impairment (hearing and vision) was associated with higher levels of depression (odds ratio [OR] = 2.980, 95% confidence interval [CI]: 2.170–4.091) and anxiety (OR = 2.636, 95% CI: 1.902–3.653) compared to single sensory impairment. Stratified associations by gender showed higher odd ratios for women with dual sensory loss (3.488 for depression and 3.478 for anxiety) compared to men (2.773 for depression and 1.803 for anxiety). Conclusions: Dual sensory impairment (hearing and seeing) is are associated with increased depression and anxiety. Women with dual sensory impairment showed stronger associations compared to men among adults in Spain. Interventions are needed to address vision and/or hearing impairment in order to reduce anxiety and depression especially in women. Key points: 23, 089 adults (15–103 years, 45.9% men) participated in this survey. Prevalence of depression and anxiety was 2.00–2.56 times higher in women than men. Dual sensory impairment associated with higher levels of depression and anxiety. Higher odd ratios for women with dual sensory loss.